State Policy And Practice On Ending Violence Against Women And Its Due Diligence In Indonesia: Perspective Of Civil Society Organization (Csos) - Abdul Aziz, Zarizana @ Izana (2023)
States have the obligation, under international law, to promote, protect and fulfill human rights as articulated in customary international law and treaties that a State ratifies. A State is obligated to comply with its obligations in accordance with the standards determined by the due diligence principle. In South East Asia, the due diligence principle is still academically underresearched, and even more so in relation to the accountability to end violence against women (VAW). There is an urgent need to contextualize the due diligence principle and to produce critical knowledge on the adoption and implementation of the due diligence principle in relation to VAW. The research critically analyses the evolution and development in human rights of the due diligence principle and its importance in crystallizing State obligation to eliminate VAW in Java, Indonesia. It examines Indonesia’s discharge of this obligation in Java by focusing on specific forms of VAW and analyzing how far Indonesia’s measures comply with treaty obligations. The research further examines civil society organizations’ (CSOs) perspectives and their assessment of Indonesia’s measures, achievements and challenges in compliance with its due diligence obligations. Finally it makes recommendations in areas where the due diligence principle may be particularly useful in eliminating VAW.